Sports Achievements Of Visually Impaired Students And Its Impacts On Their Psychological Aspects - Akhmad Solihin Solihin; Dedi Supriadi (JUARA : Jurnal Olahraga, 2022)
Visually impaired students and non-visually impaired students can excel in sports activities and appreciate themselves in the surrounding environment. This research will reveal the sports achievement profile of visually impaired students and their psychological impact. Survey research was conducted at SLB Negeri A Citeureup, Cimahi. Survey research used a qualitative research strategy. It used open-ended questions through interviews with 6 participants consisting of the principal, physical education teacher, class teacher, and three visually impaired students. The data collection used purposive sampling and applied Nvivo 12 Plus for Windows to analyze the data. The study results indicated that visually impaired students who excel in sports activities such as swimming and athletics positively impact themselves, especially psychologically. The leading indicators of the psychological elements are confidence, motivation and emotional stability. Still, it needs cooperation between school officials and parents to support psychological peace, especially self-confidence, inspiration, and emotional stability of visually impaired students to get a good life in their environment.